2016
DOI: 10.1139/cjpp-2016-0132
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects ofZygophyllum albumextract against deltamethrin-induced hyperglycemia and hepato-pancreatic disorders in rats

Abstract: The current study was designed to investigate the possible mechanism involved in hyperglycemia induced by chronic exposure to deltamethrin (DLM) in rat and to assess whether this damage is amenable to modulation by Zygophyllum album. DLM, a synthetic pyrethroid pesticide, was administrated at a dose of 4 mg/kg body mass, during 60 days. Compared with control, DLM showed a significant increase of blood glucose (p ≤ 0.01) and glycosylated hemoglobin levels (p ≤ 0.01) and a clear decrease (p ≤ 0.01) of insulin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 72 publications
2
12
0
2
Order By: Relevance
“…Our study has demonstrated a significant decrease in TBARS levels and an improved antioxidant enzymes activity (SOD, GSH-PX, GSSH-Red and CAT) in all tissue after Z. album extract supplementation. These finding are similar with those of Feriani et al (2016), who note a significant lowered lipid peroxidation in the pancreas in deltamethrin-induced hyperglycemic rats and an ameliorated levels of SOD, CAT and GSH-Px with Z. album extract treatment. The protective effect of Z. album extract could be explained by its ability to reduce the level of oxidative stress by the inhibition of ROS generation; Z. album extract can help to protect the β -cells structure and function in DM rats via a reduction of ROS production and the improvement of antioxidant enzymes.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our study has demonstrated a significant decrease in TBARS levels and an improved antioxidant enzymes activity (SOD, GSH-PX, GSSH-Red and CAT) in all tissue after Z. album extract supplementation. These finding are similar with those of Feriani et al (2016), who note a significant lowered lipid peroxidation in the pancreas in deltamethrin-induced hyperglycemic rats and an ameliorated levels of SOD, CAT and GSH-Px with Z. album extract treatment. The protective effect of Z. album extract could be explained by its ability to reduce the level of oxidative stress by the inhibition of ROS generation; Z. album extract can help to protect the β -cells structure and function in DM rats via a reduction of ROS production and the improvement of antioxidant enzymes.…”
Section: Discussionsupporting
confidence: 90%
“…However, Z. album extract exhibited a notable decrease in HbA 1 C of DM rats, which reflects the beneficial action of this extract in control of diabetes complications. Moreover, Feriani et al (2016) showed that administration of methanoic extract Z. album leaves for 60 days prevented a significant elevation in HbA 1 C, thereby increasing the level of hemoglobin in deltamethrin-induced-hyperglycemic treated rats. This could be due to the restoration of blood glucose level, consequently reducing the level of hemoglobin glycosylation during the experimental period.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…En effet, une synthèse accrue du TNF-α et de l'IL-6 est observée, ce qui pourrait être due à l'augmentation du stress oxydatif par l'intermédiaire des cellules immunitaires activées [46]. Il est bien établi que le cholestérol provoque une inflammation et les métabolites oxydés du cholestérol peuvent prendre part à la stimulation de l'expression des marqueurs de l'inflammation [47]. De plus, l'homocystéine agit contre l'inflammation induite -par le cholestérol in vivo chez le rat.…”
Section: Tnf- Homocystéine Et Protéine C-réactive (Crp)unclassified
“…De plus, l'homocystéine agit contre l'inflammation induite -par le cholestérol in vivo chez le rat. Cet effet pourrait être médié par un processus lié à l'activateur du plasminogène tissulaire [47]. Par ailleurs, les travaux de Feriani et al, [48] ont également montré que, chez le rat, l'induction du diabète expérimental par la deltaméthrine, entraine une inflammation avec des teneurs élevées en CRP et TNF-α.…”
Section: Tnf- Homocystéine Et Protéine C-réactive (Crp)unclassified